A Randomized Controlled Trial on the Outcome in Comparing an Alginate Silver Dressing with a Conventional Treatment of a Necrotizing Fasciitis Wound - Jarernchon Meekul (2018)
© 2017 SAGE Publications. Necrotizing fasciitis (NF) is a high morbidity and mortality disease and also demands high economic resources. The standard treatment of NF is surgical debridement and proper dressing for wound bed preparation. The efficacy of silver alginate dressing can inhibit the growth of microorganisms and keep the environment clean for wound bed preparation. However an optimal dressing to manage such wounds has yet to emerge. NF patients who were admitted between April 2013 and May 2016 were randomized to have wound dressing using either silver dressing (Ag group) or normal saline solution gauze (NSS group). The 4 main outcomes for comparison between the 2 groups were the duration of wound bed preparation, total cost during hospital stay, the duration of hospital stay, and the pain score. Thirty-nine patients were included in the study: 19 patients in the NSS group and 20 patients in the Ag group. The mean duration of wound bed preparation in the NSS group was 31.87 days, and in Ag group it was 21.39 days, but this trend was not statistically significant (P =.057). The mean cost of treatment in the NSS and Ag groups was not significantly different (P =.434; US$3308.83 and US$2647.82, respectively). The duration of hospital days in the 2 groups was not significantly different either (29.19 days [NSS group] and 20.99 days [Ag group]; P =.222). The pain score was significantly lower in the Ag group than those in the NSS group. Although silver dressing seems to be expensive, the cost of total treatment during hospital stay and the duration of hospital stay were not significantly different between groups. However, the mean duration of wound bed preparation seems to trend favoring toward the silver dressing group.